Polymorphism in the IL4R gene and clinical features are associated with glioma prognosis: Analyses of case-cohort studies. Issue 31 (August 2016) - Jin, Tian bo; Du, Shuli; Zhu, Xi kai; Li, Gang; Ouyang, Yongri; He, Na; Zhang, Zhiying; Zhang, Yuan; Kang, Longli; Yuan, Dongya
Abstract : Abstract: Inflammatory gene polymorphisms may be associated with glioma risk. The purpose of this study was to analyze effects of certain inflammatory gene and some clinical factors on patient survival. The clinical information of 269 glioma patients conceived operation from September 2010 to May 2014 to decide the 1-, 3-year survival rates according to follow-up results and analyze age, gender, the WHO classification, extent of surgical resection, radiotherapy and chemotherapy factors effects on prognosis. Survival distributions were estimated by using the Kaplan–Meier method and difference in the survival was tested using the log-rank test. To estimate the association between the IL4, IL13, IL10, IL4R SNPs, and PFS and OS in glioma, the HR and 95% CI were calculated by univariate Cox proportional hazards model. Multivariate Cox model were performed to compute adjusted HR and 95% CI. All data was analyzed with SPSS17.0 package. Extent of surgical resection, chemotherapy, and age are an important factor in glioma overall survival and progression-free survival overall. Extent of surgery and chemotherapy are important factors in astrocytoma overall survival. Univariate analysis showed that IL4R rs1801275 was significantly associated with overall survival of glioma and astrocytoma patients ( P < 0.05). Multivariate Cox regression analysis showed that IL4R rs1801275 GG genotype could increase the death risk of glioma and astrocytoma patients (Glioma: hazard ratio [HR]: 4.897, 95% confidence limits [95% CI]: 1.962–12.222, P = 0.001; Astrocytoma: HR: 15.944, 95% CI: 4.019–63.253, P < 0.05). Our research results showed that extent of surgical resection, age, and chemotherapy affect the prognosis of glioma. The IL4R gene may affect the survival of glioma patients.